The Influence of Pressure on the Intrinsic Dissolution Rate of Amorphous Indomethacin - Korbinian Löbmann; Konstantina Flouda; Danwen Qiu; Theodosia Tsolakou; Wenbo Wang; Thomas Rades (MDPI AG, 2014)
New drug candidates increasingly tend to be poorly water soluble. One approach to increase their solubility is to convert the crystalline form of a drug into the amorphous form. Intrinsic dissolution testing is an efficient standard method to determine the intrinsic dissolution rate (IDR) of a drug and to test the potential dissolution advantage of the amorphous form. However, neither the United States Pharmacopeia (USP) nor the European Pharmacopeia (Ph.Eur) state specific limitations for the compression pressure in order to obtain compacts for the IDR determination. In this study, the influence of different compression pressures on the IDR was determined from powder compacts of amorphous (ball-milling) indomethacin (IND), a glass solution of IND and poly(vinylpyrrolidone) (PVP) and crystalline IND. Solid state properties were analyzed with X-ray powder diffraction (XRPD) and the final compacts were visually observed to study the effects of compaction pressure on their surface properties. It was found that there is no significant correlation between IDR and compression pressure for crystalline IND and IND-PVP. This was in line with the observation of similar surface properties of the compacts. However, compression pressure had an impact on the IDR of pure amorphous IND compacts. Above a critical compression pressure, amorphous particles sintered to form a single compact with dissolution properties similar to quench-cooled disc and crystalline IND compacts. In such a case, the apparent dissolution advantage of the amorphous form might be underestimated. It is thus suggested that for a reasonable interpretation of the IDR, surface properties of the different analyzed samples should be investigated and for amorphous samples the IDR should be measured also as a function of the compression pressure used to prepare the solid sample for IDR testing.